Stimuli‐Driven Insulator–Conductor Transition in a Flexible Polymer Composite Enabled by Biphasic Liquid Metal. Issue 43 (19th September 2021) - Liu, Huaizhi; Xin, Yumeng; Bisoyi, Hari Krishna; Peng, Yan; Zhang, Jiuyang; Li, Quan
Abstract: Metal–polymer composites (MPCs) with combined properties of metals and polymers have achieved much industrial success. However, metals in MPCs are thought to be ordinary and invariable electrically conductive fillers in supportive polymers to show limited use in modern technologies. This work that is disclosed here, for the first time, introduces stimuli‐driven transition from biphasic to monophasic state of liquid metal into polymer science to form dynamic soft conductors from the binary metal–polymer composites. The binary metal that exhibits temperature‐driven reversible transition between solid and liquid states via a biphasic state is fabricated. A conducting stretchable polymer composite is developed using the judiciously chosen biphasic binary metal that undergoes conductor to insulator transition upon stretching. Insulating stretched films become conducting upon heating. A "tube" model elegantly describes such distinctive deformation/temperature‐dependent behaviors. Moreover, the conducting polymer composite shows decrease in its resistance upon increasing the sample temperature. The resistance can be tuned from 1 to 10 8  Ω depending on the state of binary metal in the phase diagram. This work would build the intimate and interesting connection between metal phases and polymer science toward next‐generation soft conductors and beyond. Abstract : An interesting phase transition of biphasic metals in stretchable polymers to form unique stimuli‐driven soft conductors is reported. The electrical and mechanical properties of the composites are greatly related to the dynamic solid–liquid phase transition of a binary metal (BM). Such equilibrium of phase transition can be conveniently and precisely mediated via temperature or atomic composition according to the phase diagram of the BM.